Prostate cancer cells express more androgen receptor (AR) following androgen deprivation, improving recognition by AR-specific T cells - Olson, Brian M. (Cancer Immunol Res, 2017)
Androgen deprivation is the primary therapy for recurrent prostate cancer, and agents targeting the androgen receptor (AR) pathway continue to be developed. Because androgen-deprivation therapy (ADT) has immmunostimulatory effects as well as direct antitumor effects, AR-targeted therapies have been combined with other anti-cancer therapies, including immunotherapies. Here, we sought to study whether an antigen-specific mechanism of resistance to ADT (overexpression of the AR) may result in enhanced AR-specific T-cell immune recognition, and whether this might be strategically combined with an antitumor vaccine targeting the AR. Androgen deprivation increased AR expression in human and murine prostate tumor cells in vitro and in vivo. The increased expression persisted over time. Increased AR expression was associated with recognition and cytolytic activity by AR-specific T cells. Furthermore, ADT combined with vaccination, specifically a DNA vaccine encoding the ligand-binding domain of the AR, led to improved antitumor responses as measured by tumor volumes and delays in the emergence of castrate-resistant prostate tumors in two murine prostate cancer models (Myc-CaP and prostate-specific PTEN-deficient mice). Together, these data suggest that ADT combined with AR-directed immunotherapy targets a major mechanism of resistance, overexpression of the AR. This combination may be more effective than ADT combined with other immunotherapeutic approaches.